Prevalence And Early Detection Of Avascular Necrosis In Post-COVID-19 Patients With Hip Pain (The Review of Diabetic Studies, 2025)
Background: Post-COVID-19 patients frequently report persistent hip pain, potentially signaling avascular necrosis (AVN) due to COVID-19-associated coagulopathy or corticosteroid use. Early detection is critical to prevent irreversible joint damage.Objective: This study evaluates AVN prevalence, staging, and diagnostic accuracy of MRI versus X-ray in this population.Methods: In this prospective observational study, 50 patients with post-COVID hip pain (mean age 45 ± 12 years; 60% male) underwent clinical evaluation, X-ray, and 1.5T MRI (T1-weighted, STIR sequences). AVN was staged using the Ficat and Arlet classification. Statistical analyses included multivariate logistic regression (adjusting for age, gender, comorbidities) and inter-rater reliability (Cohen’s κ). Ethical approval (IRB-2023-045) and informed consent were obtained.Results: MRI detected AVN in all patients (86% early-stage: 47% Stage I, 39% Stage II). Males had higher AVN prevalence (OR=2.1, 95% CI: 1.3–3.4; p=0.032). Comorbidities significantly increased risk: diabetes (aOR=3.2, 95% CI: 1.4–7.1; p=0.014), hypertension (aOR=2.8, 95% CI: 1.2–6.5; p=0.028). MRI sensitivity (100%) surpassed X-ray (32%; McNemar’s χ²=38.4, p